Leisure Preferences and Well-Being in Wellness Tourism: Insights from Voluntary Simplifiers - Iqra; Muhammad Abrar; Rizwan Shabbir (Journal for Social Science Archives, 2025)
This study explores the psychological well-being of individuals who adopt a voluntary simplicity lifestyle (VSL) to achieve both hedonic and eudaimonic well-being within the context of wellness tourism. It also examines the mediating effect of leisure involvement on the association between VSL and psychological well-being. A total of 424 responses were collected from wellness tourists who identified as simplifiers via purposive sampling. The data were analyzed using Structural Equation Modelling (SEM) with SmartPLS 4.0. Findings show that a VSL has a significant positive effect on both hedonic and eudaimonic well-being. Moreover, leisure involvement was found to positively mediate the relationship between VSL and well-being. The study also offered meaningful insights into the emerging wellness tourism industry by highlighting the importance of promoting sustainable tourism practices aligned with simplifiers’ internal values. It also provides industry practitioners with valuable guidance to better understand individuals’ preferences for leisure involvement and to enhance their psychological well-being, thereby building long-term relationships with wellness tourists.